PERBEDAAN NILAI SATURASI OKSIGEN PASIEN PPOK MENGGUNAKAN PURSED LIP BREATHING DAN 6 MINUTES WALK EXERCISE - suyanto suyanto; Venia Evika Al Islami (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Airway obstruction in COPD patients results in decreased oxygen saturation (SPO2) values. COPD non-pharmacological therapy with pursed lip breathing and 6 minutes walk exercise can theoretically increase the functional capacity of the lungs and have an impact on the value of oxygen saturation in the blood of unknown difference. Therefore the study aims to determine the difference in oxygen saturation values ​​between pursed lip breathing and 6 minutes walk exercise in COPD patients at the Central Pulmonary Health Center (BBKPM) Surakarta. Method: This research is a quasi-experimental study using two groups of pre and post test design. COPD patients treated at BBKPM Surakarta became the study population whose samples were taken by purposive sampling technique of 60 respondents. Data were analyzed using the Shapiro-Wilk normality test and then performed a parametric statistical test using the Mann Whitney test Results: The results showed that the average SPO2 value of pre and post in the pursed lip breathing intervention group increased 2.69%, while for the intervention group 6 minutes walk exercise increased an average of 1.71%. There is a significant difference in the average SPO2 value between pursed lip breathing and 6 minutes walk exercise which results sig (2-tailed) 0,000. Conclusion: The average SPO2 value of the pursed lip breathing intervention group was higher than the 6 minutes walk exercise group and it was proven that the difference was significant